Effectiveness and Safety of a Thermosensitive Hydrogel Cultured Epidermal Allograft for Burns. (December 2017) - Yoon, Jaechul; Yang, Hyeong-Tae; Yim, Haejun; Cho, Yong-Suk; Kym, Dohern; Hur, Jun; Chun, Wook; Lee, Jong-Wook; Yoon, Chunjae
ABSTRACT: OBJECTIVE: To retest the safety and effectiveness of a thermosensitive hydrogel-type cultured epithelial allograft (KeraHeal-Allo; MCTT, Seoul, South Korea) and identify the subjective experience of patients and doctors with this product. DESIGN AND SETTING: Prospective interventional phase 3 study in 3 burn centers near Seoul, South Korea. PATIENTS: Thirty-three patients with deep second-degree burns larger than 200 cm 2 (for intervention and control sites of 100 cm 2 each) were enrolled. INTERVENTION: A cultured epithelial allograft containing 2 × 10 7 /1.5 mL keratinocytes was applied to each patient's intervention site. Three principal investigators (1 in each institution) evaluated the effectiveness of the allograft at their institution and the others'. Researchers administered a subjective satisfaction survey during each patient's last visit. MAIN OUTCOME MEASURE: The primary end point of the study was the re-epithelialization period. MAIN RESULTS: The re-epithelialization period for the intervention was 2.8 ± 2.2 days faster than that of control sites at other institutions ( P < .001) and 2.5 ± 3.4 days faster than that of control sites in the same institution ( P < .001). There were no reported adverse events. Satisfaction scores provided by patients and doctors showed significantly high scores on all items. CONCLUSUIONS: This type of cultured epithelial allograft is safe and well received by patients and providers and promotes re-epithelialization.